PERENCANAAN STRUKTUR ATAS BANGUNAN GUDANG BAJA BERDASARKAN METODE LRFD DI KEDIRI - Silviana Rohmatin; Fauzie Nursandah; Dwifi Aprillia Karisma; Mahardi Kamalika Khusna Ali (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
The construction of Kediri Airport will have an impact on increasing the economy which will trigger the development companies in the production sector to accelerate. This causes an increase in the need for warehouses as supporting facilities for various production and industrial activities. The purpose of this research is to design a warehouse with steel construction using the LRFD method. IWF and C profile steel materials are used in the warehouse superstructure planning, and SAP2000 version 14 software is used for structural analysis calculations. The data warehouse has a size of 22 x 102 meters with a building height of 15.2 meters with a ground floor of 12 meters and a roof of 3.2 meters. The calculation results show that the dimensions of the cross-section that are safe from earthquakes are profiles for columns and rafters using IWF 350.350.12.19, and gording using C 150x65x20x3.2. Planned beam-column connections using plates with a thickness of 10 mm with a bolt diameter of 16 mm totaling 6 pieces, while beam-column connections using plates with thickness 12 mm with bolt diameter 20 mm totaling 4 units. So that the design can be used as a reference in the construction of warehouses that are strong and safe, especially against earthquakes.